The National Housing Policy And Sustained Development of The Peoples With Architectural Value: The Case of The Holy Spirit People, District of Antioquia, Province of Huarochirí. Lima. 2016 - Gomez de la Torre Salas, Cesar Enrique (2020)
The study aimed to identify the national housing policy that is related to the sustained development of the town with architectural value: case of Pueblo Espíritu Santo, District of Antioquia, Province of Huarochirí, Lima - 2016. The investigation was correlational, the descriptive level and the method were hypothetical deductive with a population of 965 officials of the Provincial Municipality of Huarochirí, officials of the District Municipality of Antioquia and residents of the District of Antioquia and a sample of 275 people randomized among officials of the Provincial Municipality of Huarochirí, officials of the District Municipality of Antioquia and residents of the district of Antioquia. The observation technique and the survey were used as an instrument of the study. From the study of hypothesis contrast between the variables: the national housing policy and the sustained development of the town with architectural value, an Asymptotic Significance value of 2.15% was obtained for a significance level of 5%, as the value obtained with the critical value according to the level of significance the null hypothesis was rejected and the working hypothesis was accepted. After carrying out the investigation, it was concluded that, according to Pearson’s correlation study, it was a value of 0.8993 indicating that there is a Very High Level of correlation between: National housing policy and the sustained development of peoples With architectural value: case of Pueblo Espíritu Santo, of the District of Antioquia, Province of Huarochirí, Lima - 2016.